The Role Of Perceived Trust In Mediating The Influence Of Fintech, Financial Influencers, And Investment Motivation On The Investment Decisions Of Ikatan Saham Pemula Members In Jepara Regency - Muhammad Alfain Faza Zakiyya; Anna Widiastuti; Mohamad Rifqy Roosdhani (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study aims to analyze the influence of FinTech, Financial Influencers, and investment motivation on investment decisions, positioning perceived trust as a mediating variable. The research focuses on members of the Beginner Stock Association (Ikatan Saham Pemula or ISP) in Jepara to understand the behavior of retail investors in a non-metropolitan area. This study employs a quantitative approach with an explanatory causal design. Data collection was conducted by distributing questionnaires to 100 respondents who are active members of ISP Jepara using a saturated sampling technique. The results indicate that FinTech, Financial Influencers, and investment motivation have a positive and significant direct effect on investment decisions. Furthermore, perceived trust has a positive and significant effect on investment decisions and was proven to significantly mediate the relationship between FinTech, Financial Influencers, and investment motivation with investment decisions. These findings indicate that trust is a crucial psychological mechanism that transforms technological convenience and social information into tangible investment actions for novice investors.